1999
DOI: 10.1007/s001680050105
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between travel time and travel distance of commuters

Abstract: Abstract. This paper gives a detailed empirical analysis of the relationships between di¨erent indicators of costs of commuting trips by car: di¨erence as the crow¯ies, shortest travel time according to route planner, corresponding travel distance, and reported travel time. Reported travel times are usually rounded in multiples of ®ve minutes. This calls for special statistical techniques. Ignoring the phenomenon of rounding leads to biased estimation results for shorter distances. Rather surprisingly, the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 8 publications
6
48
1
Order By: Relevance
“…Some other results are that older people drive slower, that trips made during weekends are faster than trips made on working days, and that male commuters drive slightly faster than female commuters. The latter is consistent with the literature (see, e.g., Rietveld et al 1999;Van Ommeren and Dargay 2006).…”
Section: Speedsupporting
confidence: 93%
See 1 more Smart Citation
“…Some other results are that older people drive slower, that trips made during weekends are faster than trips made on working days, and that male commuters drive slightly faster than female commuters. The latter is consistent with the literature (see, e.g., Rietveld et al 1999;Van Ommeren and Dargay 2006).…”
Section: Speedsupporting
confidence: 93%
“…We select the trips longer than 10 km to increase the probability that a trip takes place partly on highways. In order to control for carpooling effects, we control for the number of people in the vehicle (Rietveld et al 1999). Seasonal effects are captured by seasonal dummy variables.…”
Section: Data and Model Specificationmentioning
confidence: 99%
“…Most of them found that individuals substantially overstate travel times (e.g. O'Farrell and Markham, 1974;Burnett, 1978;Henley et al, 1981;MVA Consultancy, 1987;Rietveld et al, 1999;Van Exel and Rietveld, 2009). Based on this evidence, they usually conclude that travel times are perceived as longer than they actually are.…”
Section: Introductionmentioning
confidence: 99%
“…Van Exel and Rietveld, 2009) or the possibility that actual travel times might have been measured wrongly (e.g. Rietveld et al, 1999) as plausible explanations for the overstated travel times. Consistent with the results obtained in these earlier studies, also we find that travel times are strongly overreported, by a factor of 1.5 on average.…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, we interact the congestion variable with rush hour as well as with a rain dummy, as one may expect that rain may have stronger negative effects during rush hours on congested roads. In order to control for carpooling effects, we control for the number of people in the vehicle (Rietveld et al, 1999). Seasonal effects are captured by seasonal dummy variables.…”
Section: Data and Model Specificationmentioning
confidence: 99%